Estado nutricional, risco cardiovascular e a presença de comorbidades em participantes das ações do NASF do município de Candói, Paraná, Brasil - Lefchak, Fernando Juraski (2020)
Introduction: Some anthropometric indicators are characterized by being easily applied and widely used to assess obesity and body fat distribution, constituting one of the first steps to identify initial health risk. Objective: To assess and identify the frequency of general and abdominal obesity using anthropometric indicators and to verify the presence of comorbidities in individuals who participated in the NASF educational meetings and activities in the city of Candói, Paraná. Methodology: This is a quantitative and cross-sectional study, with the application of a questionnaire to find out about comorbidities and to characterize the sample by measuring weight, height and waist circumference (WC), in addition to determining the body mass index (BMI) and waist-to-height ratio (WHtR). In the association analyzes, the chisquare test was used followed by the calculation of the odds ratios. Results: Most of the sample was classified as overweight/obesity (69.2%), based on BMI, and showed high rates of abdominal obesity by WC and WHtR. The increased WC values were observed in 83.01% of the patients. Regarding WHtR, the adequate value was verified in only 14.5% of the participants. The associations between the anthropometric indices and the other variables showed statistically significant differences in relation to the age of the participants, revealing a higher frequency of increased WHtR in patients aged 60 years or older (RC = 8.53, p = 0.01). Among the comorbidities, the highlight was the presence of systemic arterial hypertension. Conclusion: In addition to the high frequencies of general obesity, abdominal obesity and the presence of comorbidities, such as systemic arterial hypertension, the WHtR was the anthropometric index capable of suggesting increased cardiometabolic risk in the elderly. In this sense, this study shows the ability to characterize users of the public health system with the potential for the development of cardiovascular disease through the use of low-cost anthropometric tools, and thus be able to support corrective actions at the level of municipal public policies.